Luso-tropicalism as a social representation in Portuguese society: Variations and anchoring. (January 2018) - Valentim, Joaquim Pires; Heleno, Ana Maria
Abstract: Luso-tropicalist assumptions include the idea of a special skill that Portuguese people have for harmonious relations with other peoples, their adaptability to the tropics and their inherent lack of prejudice. Linked with colonial ideologies, these ideas were broadly disseminated in Portuguese society after the Second World War, and they still shape social knowledge. In this article we present a psychosocial study on this issue. In the framework of social representations theory, this study aims at: (1) identifying organising principles of the social representations of luso-tropicalism among Portuguese participants; (2) investigating their anchoring in intergroup attitudes, attitude towards immigration, evaluation of colonised peoples and Portuguese colonisers, nationalist self-description and explanations for the lesser success of immigrants. For this purpose, a survey was conducted with 148 Portuguese participants. We found four dimensions of luso-tropicalism: harmonious relations, colonial past, ability to adapt and cultural integration. We can ascertain an association of these organising principles (except for cultural integration) with general prejudice towards different groups living in Portugal. At this level, these results clearly contradict the luso-tropicalist assertions about the absence of prejudice. The overall anchoring results are discussed in the framework of a psychosocial approach to luso-tropicalism as a social representation and its repercussions in contemporary societies, in particular its role in justifying the expression of prejudice in Portuguese society, as well as in different issues of current intergroup relations.